Microsoft Windows Movie Maker 2 : Visual Quickstart Guide - Ozer, Jan (Peachpit Press, 2004)
Just because you have the built-in software to transform your homemade videos into compelling, creative content doesn't necessarily mean you have the know-how to do so. For that you need this no-nonsense task-based guide. In these pages video guru Jan Ozer uses simple, step-by-step instructions peppered with plenty of visual aids and loads of time-saving tips to show you how to use Microsoft's Movie Maker 2 video-editing software (which is included with Windows XP) to edit your videos and share them with family and friends. Providing a visual approach to a visual product, Jan shows you how to start making movie magic instantly and effortlessly with the transitions, title options, and 2-D special effects included in Movie Maker 2. You'll learn how to create wipes, dissolves, freeze frames, and more in the process of producing a finished product that you'll be proud to email to friends, post on your Web site, or copy to CD or DVD.